Hypertension is associated with increased post‐exercise albuminuria, which may be attenuated by an active lifestyle. Issue 8 (8th July 2019) - Grupper, Ayelet; Ehrenwald, Michal; Schwartz, Doron; Berliner, Shlomo; Shashar, Moshe; Baruch, Roni; Schwartz, Idit F.; Rogowski, Ori; Zeltser, David; Shapira, Itzhak; Shenhar‐Tsarfaty, Shani
Abstract: Albuminuria is a known marker for endothelial dysfunction and cardiovascular events, even below the threshold of moderately increased albuminuria (MIA). Post‐exercise increased albuminuria may precede the appearance of rest MIA, enabling detection of early injury. Modifying lifestyle for a population at risk for MIA is therefore of interest. Our aim was to evaluate post‐exercise albuminuria in hypertensive compared with normotensive individuals and to analyze the effect of an active lifestyle on rest and post‐exercise albumin excretion. The study cohort consisted of 3931 adults who participated in a health‐screening program. Albuminuria was measured as urine albumin‐to‐creatinine ratio (ACR). Lifestyle was divided into three groups: non‐active, less‐active, and active according to regular sport activity, categorized as follows: none, <2.5 and ≥2.5 hours per week. Mean age was 47.7 years, and 31.2% (n = 1228) were diagnosed with hypertension. Both rest and post‐exercise ACR were higher in hypertensive compared to normotensive participants. Rest ACR was higher in non‐active compared to less‐active and active hypertensive participants. Hypertensive participants with an active lifestyle had significantly lower post‐exercise and delta ACR compared to less‐active and non‐active hypertensive participants. Parameters related to delta ACR in hypertensive participants were increased age, BMI, and diabetes, while active lifestyle and fitness (measured as METS achieved by a stress test) were protective. In conclusion, there is an association between hypertension and increased albumin excretion post‐exercise, which can be attenuated with an active lifestyle.